2021
DOI: 10.3390/antiox10071117
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Extract (POMx) Induces Mitochondrial Dysfunction and Apoptosis of Oral Cancer Cells

Abstract: The anticancer effect of pomegranate polyphenolic extract POMx in oral cancer cells has rarely been explored, especially where its impact on mitochondrial functioning is concerned. Here, we attempt to evaluate the proliferation modulating function and mechanism of POMx against human oral cancer (Ca9-22, HSC-3, and OC-2) cells. POMx induced ATP depletion, subG1 accumulation, and annexin V/Western blotting-detected apoptosis in these three oral cancer cell lines but showed no toxicity to normal oral cell lines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 61 publications
5
24
0
Order By: Relevance
“…The antiproliferative effect of the pomegranate phenolic extract was also observed against human oral cancer. The extract triggered the dysfunction of the mitochondria by damaging their membrane potential and inducing the apoptotic mechanism [53] Chlorogenic acid is an interesting antioxidant molecule due to its wide spectrum of healthy effects on some pathologies, from diabetes to cardiovascular disease and cancer [54]. The oral administration of green coffee, particularly rich in chlorogenic acid, in hypertensive rats reduced the systolic blood pressure dose dependently without inducing any modification in the normotensive control group [55].…”
Section: Discussionmentioning
confidence: 99%
“…The antiproliferative effect of the pomegranate phenolic extract was also observed against human oral cancer. The extract triggered the dysfunction of the mitochondria by damaging their membrane potential and inducing the apoptotic mechanism [53] Chlorogenic acid is an interesting antioxidant molecule due to its wide spectrum of healthy effects on some pathologies, from diabetes to cardiovascular disease and cancer [54]. The oral administration of green coffee, particularly rich in chlorogenic acid, in hypertensive rats reduced the systolic blood pressure dose dependently without inducing any modification in the normotensive control group [55].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is tightly associated with apoptosis and other forms of cell death. It has been shown that pomegranate extract induced adenosine triphosphate (ATP) depletion, subG1 accumulation, and apoptosis in oral cancer cell lines but showed no toxicity to normal oral cells [18]. The apoptotic mechanisms involved mitochondrial membrane potential disruption and mitochondrial superoxide generation associated with the differential downregulation of several antioxidant gene mRNA/protein expressions and mitochondrial DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…When antioxidant signaling is suppressed, ROS are generally developed. For example, pomegranate extract downregulated several antioxidant signaling pathways, enhancing oxidative stress, in oral cancer cells [ 50 ]. Accordingly, SK2 may downregulate the antioxidant signaling pathway, inducing ROS generation.…”
Section: Discussionmentioning
confidence: 99%